Reaching for the sky : empowering girls through education - Sahni, Urvashi (Brookings Institution Press, 2017)
Since 2003 a privately funded high school has provided desperately needed education for girls from impoverished families in Lucknow, the capital and largest city in Uttar Pradesh, in northeast India. Urvashi Sahni, the founder of Prerna Girls School, tells the stories of how the school has changed the lives of more than 5,000 girls and their families. Most important, this book tells those stories from the perspectives of the girls themselves, rather than through a remote academic perspective. -- publisher's website.